Qualidade de vida de trabalhadores mototaxistas de Aparecida de Goiânia - Freitas, Luciano Ferreira (2015)
This study aims to evaluate the quality of life as well as the relationship of this with the socioeconomic and demographic profile and the length of service of workers motorcycle taxi drivers in the city of Aparecida de Goiânia-GO. For this, we carried out an analytical study of the quantitative cross-sectional with a sample of 133 male motorcycle taxi drivers. To check the profile of these workers, a sociodemographic questionnaire and the socioeconomic questionnaire was applied, Criteria of Economic Classification Brazil (CCEB). To assess quality of life, the WHO Quality of Life (WHOQOL-BREF) questionnaire and the Short Form Health Survey (SF-36) were used. Regarding sociodemographic profiles, there was a predominance of workers, married (53.4%), with up to two children (78.9%), aged 18-40 years old (56.4%), primary school education(64 7%), between one and five years of professional practice (57.9%), and belonging to the C economic class (66.2%). Concerning quality of life, WHOQOL-Bref, it was found that the domain "environment" (52.09) and the domain "social relations" (68.23) were the ones with lowest score and the best scores obtained were in "physical" domain (74.89) and "psychological" (70.52). In the SF-36, the domain "pain" (49.59) is the most negative impact on the quality of life of these professionals and the domain "functional capacity" (81.17) was the one who got the best score. Comparing the demographic data and the length of service with the quality of life WHOQOL-Bref, significant differences in the field "environment" (p = 0.029), indicating that the group with the lowest function of time had worse quality of life that the group with greater seniority. In the SF-36, there was a significant difference in the fields "vitality" (p = 0.025) and "mental health" (p = 0.005) relative to the variable "marital status" in which the married participants had better quality of life in these areas. There was also a significant difference on "vitality" (p = 0.029) relative to the variable "age in years", indicating that the age group up to 40 years had worse quality of life compared to the older group. Compared to the variable "schooling" there was significant difference in the field "general health" (p = 0.047) in those with primary education had a poorer quality of life to those with high school. There was a significant difference in the field "vitality" (p = 0.020) compared to the variable "function of time" in which the group with the shortest time had worse quality of life compared to the older group. When comparing the WHOQOL-Bref with socioeconomic data for all economic classes, the highest score was the "physical" domain and the lowest was in the field "environment." In the analysis of the areas of the SF-36 compared to the socioeconomic data, significant differences were found in the domain "pain" (p = 0.005), indicating the participants in classes D and E with worse quality of life compared to the B and C classes. This study has highlighted the need to implement strategies for improving the quality of life of this class of workers.